Polityka państwa wobec zagranicznych inwestorów w Polsce z uwzględnieniem jej wpływu na lokalizację bezpośrednich inwestycji na Dolnym Śląsku - Zakrzewska-Półtorak, Alicja (The state policy towards foreign investors in Poland and its impact on location of direct investment in Lower Silesia region, 2006)
The paper discusses the role of state policy towards foreign investors in Poland. The author presented dynamics of foreign direct investment inflows between 1989 and 2004, main determinants of inflow and instruments ofstate policy used to attract foreign investors. Concusions were applied to case studies of foreign direct investment location in Lower Silesia. The region has become more and more attractive to foreign investors in the last several years. Not only due to state aid but also to its endogenous resources such as: human capital, educational potential and technical, economic and social infrastructure
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 135-144